Fetal biometry for guiding the medical management of women with gestational diabetes mellitus for improving maternal and perinatal health - Rao, Ujvala; de Vries, Bradley; Ross, Glynis P; Gordon, Adrienne (Cochrane database of systematic reviews, 2019)
Gestational diabetes mellitus (GDM) is a common medical condition that complicates pregnancy and causes adverse maternal and fetal outcomes. At present, most treatment strategies focus on normalisation of maternal blood glucose values with use of diet, lifestyle modification, exercise, oral anti-hyperglycaemics and insulin. This has been shown to reduce the incidence of adverse outcomes, such as birth trauma and macrosomia. However, this involves intensive monitoring and treatment of all women with GDM. We propose that using medical imaging to identify pregnancies displaying signs of being affected by GDM could help to target management, allowing low-risk women to be spared excessive intervention, and facilitating better resource allocation. We wanted to address the following question: in women with gestational diabetes, does the use of fetal imaging plus maternal blood glucose concentration to indicate the need for medical management compared with glucose concentration alone reduce the risk of adverse perinatal outcomes? We searched Cochrane Pregnancy and Childbirth's Trials Register (29 January 2019), ClinicalTrials.gov, the World Health Organization International Clinical Trials Registry Platform (ICTRP) (both on 29 January 2019), and reference lists of retrieved studies. Randomised controlled trials, including those published in abstract form only. Studies using a cluster-randomised design and quasi-randomised controlled trials were both eligible for inclusion, but we didn't identify any. Cross-over trials were not eligible for inclusion in our review.We included women carrying singleton pregnancies who were diagnosed with GDM, as defined by the trials' authors. The intervention of interest was the use of fetal biometry on imaging methods in addition to maternal glycaemic values for indicating the use of medical therapy for GDM. The control group was the use of maternal glycaemic values alone for indicating the use of such therapy. Two review authors independently assessed trials for inclusion and assessed risk of bias. Two review authors extracted data and checked them for accuracy. Three randomised controlled trials met the inclusion criteria for our systematic review - the studies randomised a total of 524 women.We assessed the three included studies as being at a low to moderate risk of bias; the nature of the intervention made it difficult to achieve blinding of participants and personnel and none of the trial reports contained information about methods of allocation concealment (and were therefore assessed as being at an unclear risk of selection bias).In all studies, the intervention was the use of fetal biometry on ultrasound to identify fetuses displaying signs of fetal macrosomia, and the use of this information to indicate the use of medical anti-hyperglycaemic treatments. Those pregnancies were subject to more stringent blood glucose targets than those without signs of fetal macrosomia.Maternal outcomesThe use of fetal biometry in addition to maternal blood glucose concentration (compared with maternal blood glucose concentration alone) may make little or no difference to the incidence of caesarean delivery (risk ratio (RR) 0.81, 95% confidence interval (CI) 0.59 to 1.10; 2 trials, 428 women; low-certainty evidence). We are unclear about the results for hypertensive disorders of pregnancy (RR 0.80, 95% CI 0.34 to 1.89; 2 trials, 325 women) due to very low-certainty evidence. The included trials did not report on development of type 2 diabetes in the mother or maternal hypoglycaemia.Fetal and neonatal outcomesThe use of fetal biometry may make little or no difference to the incidence of neonatal hypoglycaemia (RR 0.90, 95% CI 0.57 to 1.42; 3 trials, 524 women; low-certainty evidence). Very low-certainty evidence means that we are unclear about the results for large-for-gestational age (RR 0.81, 95% CI 0.38 to 1.74; 3 trials, 524 women); shoulder dystocia (RR 0.33, 95% CI 0.01 to 7.98; 1 trial, 96 women); a composite measure of perinatal morbidity or mortality (RR 1.00, 95% CI 0.21 to 4.71; 1 study, 96 women); or perinatal mortality (RR 0.33, 95% CI 0.01 to 7.98; 1 trial, 96 women). This review is based on evidence from three trials involving 524 women. The trials did not report some important outcomes of interest to this review, and the majority of our secondary outcomes were also unreported. The available evidence ranged from low- to very low-certainty, with downgrading decisions based on limitations in study design, imprecision and inconsistency.There is insufficient evidence to evaluate the use of fetal biometry (in addition to maternal blood glucose concentration values) to assist in guiding the medical management of GDM, on either maternal or perinatal health outcomes, or the associated costs.More research is required, ideally larger randomised studies which report the maternal and infant short- and long-term outcomes listed in this review, as well as those outcomes relating to financial and resource implications.